Antioxidant and cognitive promotion effects of anthocyanin-rich mulberry ( Morus atropurpurea L.) on senescence-accelerated mice and prevention of Alzheimer's disease - Shih, Ping-Hsiao; Chan, Yin-Ching; Liao, Jiunn-Wang; Wang, Ming-Fu; Yen, Gow-Chin (The Journal of nutritional biochemistry, 2010)
In the present study, we evaluated the beneficial effect of mulberry extracts (ME), which are rich in phenolics and anthocyanins, on the induction of antioxidant enzymes and on the promotion of cognition in senescence-accelerated mice (SAMP). Six-month old SAMP8 and SAMR1 mice were fed a basal diet supplemented with 0.18% and 0.9% ME for consecutive 12 weeks. The results showed that the mice fed the ME supplement demonstrated significantly less amyloid β protein and showed improved learning and memory ability in avoidance response tests. ME-treated mice showed a higher antioxidant enzyme activity and less lipid oxidation in both the brain and liver, as compared to the control mice. Furthermore, treatment with ME decreased the levels of serum aspartate aminotransferase, alanine aminotransferase, triglyceride and total cholesterol that increase with ageing. The hepatoprotective effect of ME appeared to occur through a mechanism related to regulation of the mitogen-activated protein kinases and activation of the nuclear factor-erythroid 2 related factor 2, where the latter regulates the induction of phase 2 antioxidant enzymes and reduction of oxidative damage. Overall, supplementation of ME might be advantageous to the induction of an antioxidant defense system and for the improvement of memory deterioration in ageing animals.